A Study of The Effect of Public and Private Debt on Zambia’s Economic Growth - Bwalya Gwendoline Lombe; Lubinda Haabazoka (International Journal of Engineering and Management Research, 2024)
Public and private debt plays a critical role in bridging government financing gaps especially in developing countries like Zambia with low economic growth (World Bank, 2017). Notwithstanding this fact, public debt can however be viewed as a doubled-edged sword. Public debt has become an important problem for most countries over the last decades. Despite acquiring this level of debt, most of the country’s population has continued to live in excess poverty and only a few are successfully employed. The study utilized descriptive and correlational designs and sought to determine the relationship between the independent variables (private and public debt) and economic growth, investment and social progress index .The study utilised economic secondary data from 1964 to 2020 a period of 56years. The result found that public debt has negatively affected the rate of growth in the Zambian economy over the period of study. This implies that an increase in public debt will decrease economic growth. However, public debt impact on investment was found not significant at p value 0.05, despite the coefficient indicating a weak positive correlation. The association between private debt, investment, economic growth by GDP and NGDP was found to be positively correlated and significant p-values (0.0092<0.05). However, it was revealed that increasing the amount debt especially public debt affects and reduces the level of economic growth. The study revealed that private debt increases investment and domestic saving which means that they positively impact economic growth. Private debt by individuals and corporations was found to have positive effects on some social progress indicators such as literacy, carbon emission per capita, electricity access and GDP per capital growth. Finally, it was recommended that a scrutinizing agency should be established before the acquisition of debt. As this would help in reducing the acquisition of debts which have little significance in improving the economy.